An Analysis on Problem in Listening for Academic Communication among Students of English Language Education Department of Hamzanwadi University - Lalu Ilham Mariadi (VELES Voices of English Language Education Society, 2017)
In this study the present researcher was focus on finding and analyzing the problem in Listening for Academic Communication Subject. The present researcher used case study approach. The data was collected by using questionnaire, interview, and observation among 60 second semester students of English Language Education Department. The present researcher found there were some problems faced by the students those were the lack of vocabulary of the students, the broken headset, malfunctioned buttons, the out of dated Operational System (OS), unsound proofed room, no power supply, and the teaching technique of the lecturer. Based on the data above, it can be concluded there were some problems faced by the students in Listening for Academic Communication subject. The problems faced by the students were the lack of vocabulary, the unsustainable tools and the teaching technique. The factors of the problem in Listening for Academic Communication were caused by the students, the lecturer, and the tools.